CULTURAL BORROWING BAHASA SANSEKERTA-BAHASA BALI - Putu Wulandari Tristananda (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The word absorption in the Balinese language is a word that comes from outside theBalinese language, used in language life, both oral and written taken into Balinese vocabulary.The foreign language in Bali means Indonesian, other regional languages, and foreign languages.In absorbing this vocabulary, it is done by adjusting the pronunciation, form and structure of theBalinese language. The absorption of the language has lasted until now, in accordance with theneeds and development of culture. One language that is quite large has a role in the developmentof the Balinese language is Sanskrit. The Sanskrit vocabulary has become pervasive and hasbecome the treasury of the Balinese language.Based on a glimpse of the background in theforegoing, there are several formulation of the problems to be discussed in this paper, namely:(1) How is the process of absorbing Sanskrit into Balinese, (2) How do Balinese Vocabularyobtained from Sanskrit and (3) How changes took place from Sanskrit into Balinese. Based onthe study carried out in this paper, there are several conclusions as a result of the studies obtained,namely: (1) Balinese absorbs Sanskrit through Malay and Javanese, generally obtained fromthe word similarity category. (2) The absorption of the Sanskrit vocabulary of Balinese as one ofthe regional languages in Indonesia has undergone many changes. Categorization for this is aword originating from the Malay language which takes Sanskrit in the form of vocabulary usedin naming and the terms and words that are of a direct original from Sanskrit and even getadditional elements from Kawi or Javanese. (3) The process of entering the Sanskrit vocabularyinto the Balinese language has changed more functions as terms, designations, and names.